External Supervision System Reform In The State Of The Republic Of Indonesia - Gusman, Delfina Gusman; Nazmi, Didi Nazmi (Jurnal Dinamika Hukum, 2023)
The revelation of the engineering handling of the death case of Police Brigadier Nofriansyah Yosua Hutabarat has had an impact on raising other issues related to unprofessionalism within the Indonesian National Police such as the issue of the 303 gambling consortium, drugs, promotions associated with factions within the POLRI, luxury lifestyle, case transactions and so on The public considers that unprofessionalism within the Indonesian National Police does not only occur with individual members of the police but is already "institutionalized", the slow handling of the murder case of Police Brigadier Nofriansyah Yosua Hutabarat is suspected of having a tug-of-war of interests is an example of "institutionalized" unprofessionalism, even though this case has received attention from the President and Menkopolhukam. The regulation of some of Kompolnas' repressive powers in Presidential Regulation Number 17 of 2011 gave rise to new legal norms that increase Kompolnas' authority, this becomes out of sync and harmony with Kompolnas'.Reform of the external oversight system at the Indonesian National Police is a must by rearranging the system of recruitment, education and career paths for Polri members and officials as well as strengthening the existence of external oversight institutions (both preventive and repressive in nature) and their authority attached to Kompolnas as The National Police Agency through the revision of Law Number 2 of 2002 concerning the Indonesian National Police